(3GdeZQH aj Mdi GdeZQHs - (3Ydj Hf ehSi Hf eMeO Hf YHO Gdedc GHf SYjO, GdYfSj GdeOdLj GdeZQHj , CHh GdMSf, fhQ GdOjf,J (B685 (3g` s
(3ChdgG (B:s
(3CeG HYO MeO Gddg agPG GdcJGH GdKGfi ef GdcJGHjf GddPjf jTJed YdjgeG cJGH GdedcI GdJGLjI hgh cJGH GdCbQGW GecddI ai Mdi MUf eGOJdI s
(3BNQgG (B:s
(3CHhHcQ eMeO Hf YeQ GdCfOi bQC eYi Ydi CHj Ydi GdTGhHjf EeGe fMGI GdeZQH abO MVQJ Ydi s
(3LRA efgs
(3aj GdHWGbI GdejcQhajdejI hQO Cf GdeDda gh CHh eQ GdMLGRi hZjQgs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B26 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B249s
Keywords: (3GdJGQjNs